2023
DOI: 10.3389/fmicb.2023.1146241
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnosis of duck Tembusu virus and goose astrovirus with TaqMan-based duplex real-time PCR

Abstract: The mixed infection of duck Tembusu virus (DTMUV) and goose astrovirus (GoAstV) is an important problem that endangers the goose industry. Although quantitative PCR has been widely used in monitoring these two viruses, there is no reliable method to detect them at the same time. In this study, by analyzing the published genomes of DTMUV and goose astrovirus genotype 2 (GoAstV-2) isolated in China, we found that both viruses have high conservation, showing 96.5 to 99.5% identities within different strains of DT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Second, our RT-LAMP-based CRISPR-Cas12a assay has higher specificity than RT-LAMP solely because the Cas12a-crRNA complex specifically recognizes the target gene and discriminates nucleotide mismatches to avoid false-positive results ( Chen J. S. et al, 2018 ). Third, our assay detects DTMUV RNA with a limited detection of 3 copies/μL, which is more sensitive than reported qPCR assays of DTMUV, including the SYBR Green qPCR assay (100 copies/μL) in our study ( Yan L. P. et al, 2011 ; Yan et al, 2012 ; Yun et al, 2012 ; Wan et al, 2016 ; Chen G. Q. et al, 2018 ; Zhang et al, 2020 ; Li et al, 2023 ). Fourth, our assay can be completed within 2 h from RNA extraction to readout, which suggests that our assay is more suitable for rapid detection of DTMUV relative to conventional PCR and qPCR.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Second, our RT-LAMP-based CRISPR-Cas12a assay has higher specificity than RT-LAMP solely because the Cas12a-crRNA complex specifically recognizes the target gene and discriminates nucleotide mismatches to avoid false-positive results ( Chen J. S. et al, 2018 ). Third, our assay detects DTMUV RNA with a limited detection of 3 copies/μL, which is more sensitive than reported qPCR assays of DTMUV, including the SYBR Green qPCR assay (100 copies/μL) in our study ( Yan L. P. et al, 2011 ; Yan et al, 2012 ; Yun et al, 2012 ; Wan et al, 2016 ; Chen G. Q. et al, 2018 ; Zhang et al, 2020 ; Li et al, 2023 ). Fourth, our assay can be completed within 2 h from RNA extraction to readout, which suggests that our assay is more suitable for rapid detection of DTMUV relative to conventional PCR and qPCR.…”
Section: Discussionmentioning
confidence: 67%
“…Compared with them, the qPCR assays achieve high-throughput pathogen detection and provide a real-time readout via the qPCR instrument. Currently, some qPCR assays, such as one-step RT-qPCR assay targeting the 3′ terminal noncoding region (NCR), TaqMan-based qPCR assays targeting the E or NS1 gene and SYBR Green qPCR assay targeting the E gene, have been exploited to detect DTMUV RNA or cDNA, and these assays have limits of detection from 10 to 2.67 × 10 2 copies/μL ( Yan L. P. et al, 2011 ; Yan et al, 2012 ; Yun et al, 2012 ; Wan et al, 2016 ; Chen G. Q. et al, 2018 ; Zhang et al, 2020 ; Li et al, 2023 ). Nonetheless, both PCR-based assays and qPCR assays take at least 2 to 4 h and require special equipment, which suggests that they are not convenient for the field detection of DTMUV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common methods of SNP genotyping with qPCR is the TaqMan method [16,24]. This method remains one of the most commonly used in genotyping today [25][26][27]. This method is ideal for genotyping known polymorphisms that are allele specific in a given genome.…”
Section: Taqman Methodsmentioning
confidence: 99%
“…Astroviruses are a genetically diverse virus family notably responsible for the second most common cause of nosocomial diarrhea following rotaviruses ( Meyer et al, 2015 ), as well as substantial economic losses in the poultry industry ( Karlsson et al, 2015 ; Li et al, 2023 ). Also, astrovirus infection has been associated with encephalitis and meningitis in immunocompromised patients ( Vu et al, 2017 ) and astrovirus infection has been shown to be present in the brains of some mammals ( Chae et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%